2016
DOI: 10.5897/ijbc2016.0949
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in cowpea (Vigna unguiculata [L.] Walp.) germplasm collection from Botswana

Abstract: Characterization of cowpea (Vigna unguiculata[Areas not yet explored and those that need additional sampling were identified. The study demonstrated a significant amount of diversity among the germplasm based on the analysis of variance (ANOVA) and Shannon Weaver Diversity Index (H'). The majority of accessions had their first flowering more than 50 days after sowing and 100 days for 95% of maturity which shows that they are more inclined towards late maturing cowpeas. Early maturing accessions with less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…stenophylla flowered around 23 -64 days which confirms non-photosensitive and they may be grouped as early maturing as classified by Singh and Ajeigbe [39] and Dugje et al [40]. In contrast, Molsiwa et al [41] who worked on phenotypic variation in cowpea accessions reported a higher range of 39 -168 days for number of days to first flower. It is important to note that only accession TVNu539 flowered in 3 weeks and produced ripe pods in 4 weeks of planting, making it a potential parent when breeding for early maturity.…”
Section: Variation In Growth Traitsmentioning
confidence: 96%
“…stenophylla flowered around 23 -64 days which confirms non-photosensitive and they may be grouped as early maturing as classified by Singh and Ajeigbe [39] and Dugje et al [40]. In contrast, Molsiwa et al [41] who worked on phenotypic variation in cowpea accessions reported a higher range of 39 -168 days for number of days to first flower. It is important to note that only accession TVNu539 flowered in 3 weeks and produced ripe pods in 4 weeks of planting, making it a potential parent when breeding for early maturity.…”
Section: Variation In Growth Traitsmentioning
confidence: 96%
“…Levels of diversity among cowpea genotypes can be determined through phenotypic characterization and assessment of mineral elements and protein content (Stoilova & Pereira, 2013). Several studies using morphological, agronomic, and nutritional characteristics have evaluated diversity in cowpea populations in South Africa (SA) and International Institute of Tropical Agriculture (IITA; Gerrano et al, 2015Gerrano et al, , 2017Gerrano et al, , 2019Gerrano et al, , 2020Gerrano et al, , 2022Lazaridi et al, 2017;Mbuma et al, 2020Mbuma et al, , 2021Mbuma et al, , 2022Mofokeng et al, 2020;Molosiwa et al, 2016). For years, the Agricultural Research Council (ARC) in SA has been maintaining cowpea germplasm collection of approximately 75 accessions, with genotypes that are either locally bred or derived from other breeding programs.…”
Section: Core Ideasmentioning
confidence: 99%
“…The analysis of variance revealed significant differences among the genotypes for the ten quantitative characters indicating the presence of adequate variability, which can be exploited through selection. Different reports indicated there is substantial phenotypic variability among cowpea varieties for different characters (Animasaun et al, 2015;Cobbinah et al, 2011;Gerrano et al, 2015;Lazaridi et al, 2017;Menssen et al, 2017;Molosiwa et al, 2016).…”
Section: Analysis Of Variancementioning
confidence: 99%